2010
DOI: 10.1186/1471-2156-11-82
|View full text |Cite
|
Sign up to set email alerts
|

Gene cassette transcription in a large integron-associated array

Abstract: BackgroundThe integron/gene cassette system is a diverse and effective adaptive resource for prokaryotes. Short cassette arrays, with less than 10 cassettes adjacent to an integron, provide this resource through the expression of cassette-associated genes by an integron-borne promoter. However, the advantage provided by large arrays containing hundreds of cassettes is less obvious. In this work, using the 116-cassette array of Vibrio sp. DAT722 as a model, we investigated the theory that the majority of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…It would be interesting to test whether there is a CRP control of the integron cassettes as it has been shown that other extracellular stresses can influence cassette expression in the Vibrio superintegron (52).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to test whether there is a CRP control of the integron cassettes as it has been shown that other extracellular stresses can influence cassette expression in the Vibrio superintegron (52).…”
Section: Discussionmentioning
confidence: 99%
“…Either these cassettes are transcriptionally silent or they carry their own internal promoters. In the very long cassette arrays that characterize many Vibrio species, it appears that most cassettes are transcribed and that this transcription is enhanced by some stress treatments (90). Consequently, it seems likely that gene cassettes with internal promoters are scattered throughout the Vibrio arrays and that these help drive the expression of downstream cassettes.…”
Section: Expression Of Gene Cassettesmentioning
confidence: 99%
“…4B). However, a recent study demonstrated that some cassettes within the array can include a promoter that controls the transcription of several genes (198). To be able to maintain such large numbers of unused genes, superintegrons contain postsegregation killing systems (see "Postsegregation killing systems," below).…”
Section: Fig 3 Schematic Organization Of a Diversity-generating Retromentioning
confidence: 99%